2012
DOI: 10.1108/02651331211229750
|View full text |Cite
|
Sign up to set email alerts
|

Risk, trust, and consumer online purchasing behaviour: a Chilean perspective

Abstract: Purpose -The purpose of this study is to investigate Chilean consumers' online purchase behaviour with a specific focus on the influence of perceived risk and trust. Studies of this nature have been conducted quite extensively in developed countries and in cross-cultural comparative studies most noticeably comparing the USA with Asian countries. However, examining consumers' perceived risk and trust with online purchasing in a Latin American context is very limited. While not a cross-cultural study, this gap i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
5
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(124 citation statements)
references
References 66 publications
6
102
5
11
Order By: Relevance
“…The first group, Risk Perceptions, is composed of Product and Financial Risk perceptions of consumers. Many studies confirmed the effect of consumers' risk perceptions on online shopping intention (Bianchi and Andrews, 2012;Chang and Wu, 2012;Pi and Sangruang, 2011;Lee and Huddleston, 2009;Jay et. all, 2002;Bhatnagar et.…”
Section: Proposed Research Model and Hypothesismentioning
confidence: 72%
“…The first group, Risk Perceptions, is composed of Product and Financial Risk perceptions of consumers. Many studies confirmed the effect of consumers' risk perceptions on online shopping intention (Bianchi and Andrews, 2012;Chang and Wu, 2012;Pi and Sangruang, 2011;Lee and Huddleston, 2009;Jay et. all, 2002;Bhatnagar et.…”
Section: Proposed Research Model and Hypothesismentioning
confidence: 72%
“…Furthermore, prior research that examines the use of the Internet for commercial purposes in developed countries may not necessarily be relevant for emerging countries such as Latin America due to differing cultural dimensions and levels of development (Bianchi & Andrews, 2012;Gong, 2009;Nasco, Grandon, & Mykytn, 2008). Emerging market contexts have lower levels of economic development in comparison to developed nations (Wright, Filatotchev, Hoskisson, & Peng, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Consumers in developed countries, for instance in the USA or in some countries in Europe, have used the Internet for everyday shopping and the popularity of purchasing grocery online is increasing annually in both the USA and Western Europe (Bianchi & Andrews, 2012). As a result, there has been increasing interest in understanding consumers' behavior with online grocery shopping.…”
Section: The Specification Of Online Grocery Shoppingmentioning
confidence: 99%